IMPLEMENTASI MEDIA AJAR DIGITAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - dedi saputra (Jurnal Pengabdian Pemersatu Bangsa, 2025)
The use of digital learning media in education is an innovative effort to enhance students’ learning motivation in the digital era. This community service activity aimed to improve students’ competencies in designing and implementing digital learning media as well as to increase learning motivation. The activity was conducted at the Aula of  Universitas Islam Kebangsaan  Indonesia (UNIKI) Bireuen in September 2025, involving 34 university students as participants. The method used was a participatory approach through training and mentoring, which included preparation, implementation, assistance, and evaluation stages. The results showed that participants were able to produce various digital learning media such as instructional videos, interactive presentations, and graphic-based learning tools. In addition, there was an improvement in participants’ understanding and skills in utilizing educational technology. Learning motivation also increased, as indicated by active participation and engagement during the activity. Therefore, the implementation of digital learning media proved effective in improving both learning motivation and participants’ competencies in technology-based learning.